Hyperaccumulation of Gadolinium by Methylorubrum extorquens AM1 Reveals Impacts of Lanthanides on Cellular Processes Beyond Methylotrophy - Good, Nathan M.; Lee, Harvey D.; Hawker, Emily R.; Su, Morgan Z.; Gilad, Assaf A.; Martinez-Gomez, N. Cecilia (Frontiers in Microbiology, 2022)
Lanthanides (Ln) are a new group of life metals, and many questions remain regarding how they are acquired and used in biology. Methylotrophic bacteria can acquire, transport, biomineralize, and use Ln as part of a cofactor complex with pyrroloquinoline quinone (PQQ) in alcohol dehydrogenases. However, for most methylotrophic bacteria, use is restricted to the light Ln, ranging from lanthanum to samarium (atomic numbers 57-62). Understanding how the cell differentiates between light and heavy Ln, and the impacts of these metals on the metabolic network, will advance the field of lanthanide biochemistry and give insight into enzyme catalysis, stress homeostasis, and metal biomineralization and compartmentalization. We report robust methanol growth with the heavy Ln gadolinium by a genetic variant of the model methylotrophic bacterium Methylorubrum extorquens AM1, named evo-HLn, for “evolved for heavy lanthanides”. A single non-synonymous nucleotide polymorphism in a cytosolic hybrid histidine kinase allowed for sweeping transcriptional alterations to heavy metal stress response, methanol oxidation, central metabolism, Ln acquisition and uptake, and biosynthetic pathways for a Ln-chelating lanthanophore, PQQ, carotenoids, and toblerol. Gadolinium was hyperaccumulated by evo-HLn, resulting in an enlarged acidocalcisome-like compartment. This is the first evidence for a bacterial intracellular Ln-containing compartment that we name the “lanthasome”. Finally, due to its unique capabilities, evo-HLn can be used to further MRI imaging and bioremediation technologies. In this regard, we show gadolinium hyperaccumulation was sufficient to produce MRI contrast in whole cells, and that evo-HLn was able to readily acquire the metal from the MRI contrast agent gadolinium-DTPA.